Contribution of Multiple Inter-Kingdom Horizontal Gene Transfers to Evolution and Adaptation of Amphibian-Killing Chytrid, Batrachochytrium dendrobatidis - Sun, Baofa; Li, Tong; Xiao, Jinhua; Liu, Li; Zhang, Peng; Murphy, Robert W.; He, Shunmin; Huang, Dawei (Frontiers in Microbiology, 2016)
Amphibian populations are experiencing catastrophic declines driven by the fungal pathogen Batrachochytrium dendrobatidis (Bd). Although horizontal gene transfer (HGT) facilitates the evolution and adaptation in many fungi by conferring novel function genes to the recipient fungi, inter-kingdom HGT in Bd remains largely unexplored. In this study, our investigation detects 19 bacterial genes transferred to Bd, including metallo-beta-lactamase and arsenate reductase that play important roles in the resistance to antibiotics and arsenates. Moreover, three probable HGT gene families in Bd are from plants and one gene family coding the ankyrin repeat-containing protein appears to come from oomycetes. The observed multi-copy gene families associated with HGT are probably due to the independent transfer events or gene duplications. Five HGT genes with extracellular locations may relate to infection, and some other genes may participate in a variety of metabolic pathways, and in doing so add important metabolic traits to the recipient. The evolutionary analysis indicates that all the transferred genes evolved under purifying selection, suggesting that their functions in Bd are similar to those of the donors. Collectively, our results indicate that HGT from diverse donors may be an important evolutionary driver of Bd, and improve its adaptations for infecting and colonizing host amphibians.